Online measurement of highly oxygenated compounds from organic aerosol - E. Häkkinen; J. Zhao; F. Graeffe; N. Fauré; J. E. Krechmer; D. Worsnop; H. Timonen; M. Ehn; J. Kangasluoma (Atmospheric Measurement Techniques, 2023)
Highly oxygenated compounds are important contributors to the formation and growth of atmospheric organic aerosol and thus have an impact on Earth’s radiation balance and global climate. However, knowledge of the contribution of highly oxygenated compounds to organic aerosol and their fate after condensing into the particle phase has been limited by the lack of suitable detection techniques. Here, we present a new online method for measuring highly oxygenated compounds from organic aerosol. The method includes thermal evaporation of particles in a new inlet, the vaporization inlet for aerosols (VIA), followed by identification of the evaporated highly oxygenated compounds by a nitrate chemical ionization mass spectrometer (NO3-CIMS). The method does not require sample collection, enabling highly time-resolved measurements of particulate compounds. We evaluate the performance of the method by measuring the detection limit and performing background measurements. We estimate a detection limit of below 1 ng m−3 for a single compound and below 1 µg m−3 for SOA with the sampling setup used here. These detection limits can be improved upon by optimizing the flow setup. Furthermore, we detect hundreds of particulate highly oxygenated compounds from organic aerosol generated from different precursors. Our results are consistent with previous studies showing that the volatility of organic compounds decreases with increasing m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="46f32566b65c77f385ccc58250dc589d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-16-1705-2023-ie00001.svg" width="23pt" height="14pt" src="amt-16-1705-2023-ie00001.png"/></svg:svg> ratio and level of oxygenation and that organic aerosol consists of monomers and oligomeric compounds. By comparing the gas- and particle-phase compounds, we found indications of potential particle-phase reactions occurring in organic aerosol. Future work will focus both on further improving the sampling design and on better understanding the evaporation dynamics of the system, but already these initial tests show that the VIA coupled to the NO3-CIMS is a promising method for investigating the transformations and fate of the compounds after condensing into the particle phase.